2020
DOI: 10.1149/2162-8777/ab9a58
|View full text |Cite
|
Sign up to set email alerts
|

Role of Carbon Pre-Germanidation Implantation on Enhancing the Thermal Stability of NiGe Films Below 10 nm Thickness

Abstract: The effects of carbon on improving the thermal stability of relatively thick NiGe films were manifested in previous work. How this thermal stability can be maintained for ultrathin NiGe films i.e. below 10 nm thickness, is, however, still unknown and deserves to be explored. In this work, the effects of carbon Pre-Germanidation Implantation (PGI) on the thermal stability of ultrathin NiGe films below 10 nm thickness were systematically studied. For different thicknesses of Ni layers, as-prepared NiGe films wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…However, one major drawback of Ni x Ge y is its rough interface due to polycrystalline grains and agglomeration at high annealing temperatures (500-550 • C). It was reported that the thermal stability of Ni x Ge y on bulk Ge could be improved by pre-germanidation implantation [6], prior-germanidation fluorine implantation into Ge substrate [7], dopant segregation [8], or introducing other elements, such as titanium (Ti) [9], platinum (Pt) [10], tungsten (W) [11], tantalum (Ta) [11,12], cobalt (Co) [13], ytterbium (Yb) [14], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…However, one major drawback of Ni x Ge y is its rough interface due to polycrystalline grains and agglomeration at high annealing temperatures (500-550 • C). It was reported that the thermal stability of Ni x Ge y on bulk Ge could be improved by pre-germanidation implantation [6], prior-germanidation fluorine implantation into Ge substrate [7], dopant segregation [8], or introducing other elements, such as titanium (Ti) [9], platinum (Pt) [10], tungsten (W) [11], tantalum (Ta) [11,12], cobalt (Co) [13], ytterbium (Yb) [14], and so on.…”
Section: Introductionmentioning
confidence: 99%